STRUCTURE SHIFT IN INDONESIAN – ENGLISH TRANSLATION - I Ketut Subagia; I Made Astu Mahayana (Universitas Warmadewa, 2018)
Structure shift is one of the problems in translations. This problem is important to be dealt with because it is the most frequent category occurring at all rank in translation. Besides, in grammar structure shift can occur at all ranks. The discussion about structure shift only covers structure shift in phrase, clause, and sentence level. This research used the translation theory proposed by J.C. Catford (1965). He states that shift is departure from formal correspondence in the process of going form the SL to the TL. He also states that there are two kinds of shift in translating, namely level-shift and category-shift. Category shift means the change of formal structure of the SL, in process of translating into the TL. The data source is taken from four bilingual folklores. Data collecting used observation method and descriptive method was employed in analyzing the data. The findings show that in phrase level structure shift found only in noun and adjective phrase. The shifts in noun phrase are: H PostM PostM into PreM PreM H, H PostM into PreM H, and PreM H PostM Post M, into PreM PreM PreM H. In adjective phrase structure shift is found only one i.e. PreM H into H PostM. The structure shift in clause level is: SC into SVC, SV into SVA, and SV into SVO. In sentence level structure shift occur from simple sentence in SL into simple sentence in TL, simple sentence in SL into complex sentence in TL, complex sentence in SL into simple sentence in TL, and complec sentence in SL into complex sentence in TL.